2001
DOI: 10.1046/j.1365-2249.2001.01639.x
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of CD4+ T cells with a cytotoxic phenotype in patients with B-chronic lymphocytic leukaemia (B-CLL)

Abstract: SUMMARYAbnormal CD4/CD8 ratios and T-cell function have previously been shown in patients with B-chronic lymphocytic leukaemia (B-CLL). We have demonstrated that CD4 1 T cells containing both serine esterase and perforin (PF) are increased in the blood of these patients. Using flow cytometry, we have shown that the CD4 1 PF 1 cells were CD57 1 but lacked expression of CD28, suggesting a mature population. The same phenotype in CD8 1 T cells is characteristic of mature cytotoxic T cells. However, in contrast to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
37
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 33 publications
(35 reference statements)
11
37
0
2
Order By: Relevance
“…29,30 Our results obtained with intracytoplasmic staining confirmed that CD4 + T lymphocytes from CLL patients (n=12) produce significantly more IL-4 than those obtained from appropriate controls when activated in the presence of mitogenic anti-CD3/CD28 mAbs, (Figure 6A and B). On the contrary, CD8 + T lymphocytes from CLL patients produced significantly lower amounts of IFN-γ as compared to controls ( Figure 6A and B).…”
Section: Pd-1/pd-l1 Crosstalk Contributes To Suppressing Ifn-γ Producsupporting
confidence: 70%
“…29,30 Our results obtained with intracytoplasmic staining confirmed that CD4 + T lymphocytes from CLL patients (n=12) produce significantly more IL-4 than those obtained from appropriate controls when activated in the presence of mitogenic anti-CD3/CD28 mAbs, (Figure 6A and B). On the contrary, CD8 + T lymphocytes from CLL patients produced significantly lower amounts of IFN-γ as compared to controls ( Figure 6A and B).…”
Section: Pd-1/pd-l1 Crosstalk Contributes To Suppressing Ifn-γ Producsupporting
confidence: 70%
“…16,19,[22][23][24][25] The precise role that different T-cell subsets play in the immunodeficiency of CLL remains undetermined but functional studies have identified defects in immune synapse formation, costimulatory/accessory molecule expression and cytokine release. [15][16][17] Despite these problems, several T-cell-based therapeutic strategies have been tried in CLL including adoptive transfer of anti-CD3/anti-CD28 activated T cells, 26 T cells expressing chimeric antigen receptors, and vaccine therapy with dendritic cells pulsed with CLL-cell lysates. [27][28][29] The potential power of T cells to mediate therapeutic responses in CLL was demonstrated in a recent study using adoptive transfer of gene-modified (CD19 chimeric antigen receptor and 4-1BB) T cells.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 However, given the well-known T-cell dysfunction seen in CLL, blinatumomab may be less effective in this disease. [15][16][17] In the current study, we provide a detailed analysis of the mechanism of action of blinatumomab-induced cytotoxicity in CLL. Our findings are consistent with a model that relies upon the sequential activation of T cells and CLL cells and demonstrate that blinatumomab retains efficacy even in the presence ©2013 Ferrata Storti Foundation.…”
Section: Cd23mentioning
confidence: 99%
“…Considered that tumorreactive Cytotoxic CD4+ T cells have been a bright point in immunotherapy of tumor (Porakishvili et al, 2001;Quezada et al, 2010;Akhmetzyanova et al, 2013), so we also measured perforin production of CD8+ T cells as well as CD4+ T cells. Unfortunately, CPT showed marginal effect on CD8+ cytotoxic T cells, even though that CD8+ cytotoxic T cells are classic tumor killing cells (Ohmura et al, 2008), but enhanced perforin production of CD4+ T cells.…”
Section: Discussionmentioning
confidence: 99%